Categorization of multiple sclerosis relapse subtypes by B cell profiling in the blood - Hohmann, Christopher; Milles, Bianca; Schinke, Michael; Schroeter, Michael; Ulzheimer, Jochen; Kraft, Peter; Kleinschnitz, Christoph; Lehmann, Paul V.; Kuerten, Stefanie (Acta Neuropathologica Communications, 2014)
Introduction: B cells are attracting increasing attention in the pathogenesis of multiple sclerosis (MS). B cell-targeted therapies with monoclonal antibodies or plasmapheresis have been shown to be successful in a subset of patients. Here, patients with either relapsing-remitting (n = 24) or secondary progressive (n = 6) MS presenting with an acute clinical relapse were screened for their B cell reactivity to brain antigens and were re-tested three to nine months later. Enzyme-linked immunospot technique (ELISPOT) was used to identify brain-reactive B cells in peripheral blood mononuclear cells (PBMC) directly ex vivo and after 96 h of polyclonal stimulation. Clinical severity of symptoms was determined using the Expanded Disability Status Scale (EDSS). Results: Nine patients displayed B cells in the blood producing brain-specific antibodies directly ex vivo. Six patients were classified as B cell positive donors only after polyclonal B cell stimulation. In 15 patients a B cell response to brain antigens was absent. Based on the autoreactive B cell response we categorized MS relapses into three different patterns. Patients who displayed brain-reactive B cell responses both directly ex vivo and after polyclonal stimulation (pattern I) were significantly younger than patients in whom only memory B cell responses were detectable or entirely absent (patterns II and III; p = 0.003). In one patient a conversion to a positive B cell response as measured directly ex vivo and subsequently also after polyclonal stimulation was associated with the development of a clinical relapse. The evaluation of the predictive value of a brain antigen-specific B cell response showed that seven of eight patients (87.5%) with a pattern I response encountered a clinical relapse during the observation period of 10 months, compared to two of five patients (40%) with a pattern II and three of 14 patients (21.4%) with a pattern III response (p = 0.0005; hazard ratio 6.08 (95% confidence interval 1.87-19.77). Conclusions: Our data indicate actively ongoing B cell-mediated immunity against brain antigens in a subset of MS patients that may be causative of clinical relapses and provide new diagnostic and therapeutic options for a subset of patients.
CRIS-Team Scopus Importer:2022-08-05
Keywords: B cells; ELISPOT; MS; Predictive value; Relapse